Pengaruh Kreativitas dan Motivasi terhadap Kemandirian Belajar Siswa Kelas X di SMA Kristen Satya Wacana Salatiga - Vika Noviana Safitri (Universitas Veteran Bangun Nusantara, 2021)
ABSTRACKThe purpose of this study was to determine the effect of creativity and motivation on learning independence at Satya Wacana Christian Senior High School, Salatiga. This study used an associative method with a quantitative approach. The technique used is data collection (questionnaire). Data analysis using multiple linear regression Y = 36.706-0.143 (X1) + 0.265 (X2) based on the analysis and discussion it can be concluded that: 1) There is no influence between Creativity (X1) on Independence Learning (Y). 2) There is an influence between Motivation (X2) on Independent Learning (Y). 3.) There is an influence between Creativity (X1) and Motivation (X2) on Independence Learning (Y). This means that creativity does not contribute to learning independence while motivation contributes to increasing learning independence.Keywords : Kreativitas, Movivasi, dan Kemandirian Belajar